Penyelesaian Sengketa Melalui Abritase Dalam Perjanjian Kontrak Bisnis - Wieke Azhara Boesye; Aulia Anitami; Anidya Laspendra; Helfira Citra (GLOBAL SCIENTS PUBLISHER, 2024)
In the ever-growing business world, business contracts are the basis for legal certainty and good relations between parties. This article discusses the enforcement of business agreements in an effort to prevent disputes in court. By analyzing various real cases. Clear and detailed agreements can minimize the risk of disputes. In addition, good communication and negotiation when making legal contracts with business competitors means that there is authority over the production and use of certain services by an entity or economic group. The existence of competition law prevents monopolistic practices and unfair business competition, so that trust is obtained in the implementation of contracts, and all trust is obtained in the form of objects, property, and others. Trust is generally considered the basis of a successful relationship and is therefore very sensitive in law and business. This study aims to assist entrepreneurs in drafting and enforcing contracts to reduce the possibility of disputes and ensure more effective legal protection. Most business settlements are carried out using litigation or through a conference process. The settlement begins with filing a lawsuit with the district court and ends with a judge's decision. However, apart from settlement through the litigation process, there are also settlements through non-litigation.